2016
DOI: 10.1002/ange.201512031
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic‐Containing Phosphatidylcholines: A New Group of Arsenolipids Discovered in Herring Caviar

Abstract: A new group of arsenolipids based on cell‐membrane phosphatidylcholines has been discovered in herring caviar (fish roe). A combination of HPLC with elemental and molecular mass spectrometry was used to identify five arsenic‐containing phosphatidylcholines; the same technique applied to salmon caviar identified an arsenic‐containing phosphatidylethanolamine. The arsenic group in these membrane lipids might impart particular properties to the molecules not displayed by their non‐arsenic analogues. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…67 Two new groups of arsenolipids, arsenic-containing phosphatidylcholines (AsPC) and arsenic-containing phosphatidylethanolamine (AsPE) from herring caviar, were characterized. 68 In total, more than 20 arsenosugars and 70 arsenolipids have been identified in marine organisms that live in low phosphate and high salt environments. These organoarsenicals are not toxic for the marine plants and animals, but their function in these marine organisms is not known.…”
Section: Arsenic Metabolism: From Genes To Biogeochemical Processesmentioning
confidence: 99%
“…67 Two new groups of arsenolipids, arsenic-containing phosphatidylcholines (AsPC) and arsenic-containing phosphatidylethanolamine (AsPE) from herring caviar, were characterized. 68 In total, more than 20 arsenosugars and 70 arsenolipids have been identified in marine organisms that live in low phosphate and high salt environments. These organoarsenicals are not toxic for the marine plants and animals, but their function in these marine organisms is not known.…”
Section: Arsenic Metabolism: From Genes To Biogeochemical Processesmentioning
confidence: 99%
“…Concerning lipid fraction, several studies on brown algae have been focused on minor arsenosugar phospholipids [16][17][18], arsenic-including hydrocarbons [19,20], and free polyunsaturated fatty acids [21,22]. While the knowledge of glycolipids (GL) and PL is foremost in red algae [23], these compounds have been only partially investigated in brown algae [24].…”
Section: Introductionmentioning
confidence: 99%
“… 1 In the past decade, about 70 arsenolipids have been discovered from algae, fish oil, and caviar (Supporting Information Table S1 ). Reported arsenolipids typically include phosphatidyl-arsenosugar (AsPL), 2 arsenic-containing fatty acids (AsFAs), 3 arsenic-containing hydrocarbons (AsHCs), 4 trimethylarsenio fatty alcohols (TMAsFOHs), 5 arsenic-containing phosphatidylcholines (AsPCs), and arsenic-containing phosphatidylethanolamines (AsPEs). 6 Recent studies have found that several arsenolipids elicited cytotoxicity comparable to that of arsenite in the human bladder and liver cells.…”
Section: Introductionmentioning
confidence: 99%